Sustainability reporting quality of Indian and American manufacturing firms: A comparative analysis - Munshi, Diganta; Dutta, Sraboni (Serbian Journal of Management, 2016)
The content analysis method has been adopted to study the pattern of reporting on sustainability indicators by 10 American and 10 Indian manufacturing firms in their sustainability reports prepared as per the GRI framework and published during 2011-2013. Scores of 2, 1 and 0 have been respectively assigned for full, partial and non disclosure of sub clauses of economic, environment and social indicators to compute a SDI (sustainability disclosure index). Independent t test found a significant difference in the quality of sustainability disclosure of the sampled American and Indian manufacturing firms during 2011-13. The improvement/ deterioration in the quality of disclosure over the period were correlated with changes in performance parameters like EPS and ROA to examine if betterment in quality of sustainability reporting translates into financial performance of the firms. Multiple regression analysis was performed to determine the variables which explain the variation in the sustainability reporting quality of firms.